c-Jun N-terminal kinase signaling in aging - Li, Yihao; You, Li; Nepovimova, Eugenie; Adam, Vojtech; Heger, Zbynek; Jomova, Klaudia; Valko, Marian; Wu, Qinghua; Kuca, Kamil (Frontiers in Aging Neuroscience, 2024)
Aging encompasses a wide array of detrimental effects that compromise physiological functions, elevate the risk of chronic diseases, and impair cognitive abilities.However, the precise underlying mechanisms, particularly the involvement of specific molecular regulatory proteins in the aging process, remain insufficiently understood.Emerging evidence indicates that c-Jun N-terminal kinase (JNK) serves as a potential regulator within the intricate molecular clock governing aging-related processes. JNK demonstrates the ability to diminish telomerase reverse transcriptase activity, elevate β-galactosidase activity, and induce telomere shortening, thereby contributing to immune system aging. Moreover, the circadian rhythm protein is implicated in JNK-mediated aging. Through this comprehensive review, we meticulously elucidate the intricate regulatory mechanisms orchestrated by JNK signaling in aging processes, offering unprecedented molecular insights with significant implications and highlighting potential therapeutic targets. We also explore the translational impact of targeting JNK signaling for interventions aimed at extending healthspan and promoting longevity.